Immagini, motivi, reperti. Prospettive di iconologia letteraria in Lea Ritter Santini - Maciocci, Chiara (Status Quaestionis, 2025)
The aim of this contribution is to account for the specific methodology of literary research used by the well-known Germanist and comparatist Lea Ritter Santini; a methodology characterised by its insertion in the path of the interdisciplinary approach – between the figurative arts and literature – that was opened up in the German context by Aby Warburg and Ernst Robert Curtius, and that in Ritter Santini took on the specific form of a ‘literary iconology’. In trying to paint a theoretical picture of literary iconology, an attempt will also be made to convey the sense of survey and historical reconstruction that her comparative work on texts and images has taken on; finally shedding light on a research whose primary objective was to reconstruct, by inventorying and recording affinities, a common morphology of imagery that was to characterise the European cultural tradition, understood, with Curtius, as continuous and unitary, albeit in the ruptures of its history.